Qashidah Burdah sebagai Media Pengobatan Magis-Ekonomis - Ahmad Faidi (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
The tradition of Qashidah Burdah reading againsts sick people carried out at the East Sera village is different from the other regions. The difference is the aim of the practice which is more specific and focus to cure disease. It indicates that the tradition of Qashidah Burdah reading carried out at the East Sera village has meaning and function specifications which can not be found in other areas. East Sera society interpret Qashidah Burdah tradition as an alternatif treatment media implemented when the other media treatments (medical and shaman) are not able to cure. In addition, the tradition of Qashidah Burdah reading againsts sick person also has several functions; namely socio-economic function (this media treatment is much cheaper than the others); socio-religious function (it can strengthen monotheism, fortitude and resignation to Allah), and socio-cultural function as a medium for preserving helpfulness attitude, familiarity, and social solidarity. The existence of those functions – both latent and manifest – becomes the reason of why the tradition of Qashidah Burdah reading againsts sick people still continues to be preserved by the people of East Sera.